O092 Fibrin-based haemostatic agents for reducing blood loss in adult liver resection: a meta-analysis. (22nd July 2022) - Malik, AK; Amer, AO; White, SA; Manas, DM; Wilson, CH
Abstract: Introduction: Liver resection can be associated with significant perioperative bleeding. Fibrin based haemostatic agents (FBHAs) are bioabsorbable topical haemostatic agents used to enhance haemostasis and reduce blood loss. We performed a systematic review and meta-analysis, comparing FBHAs with the standard of care and no topical application (SoC), and comparing FBHAs with non-fibrin-based haemostatic agents (NFHAs) to evaluate their efficacy in reducing blood loss and improving perioperative outcomes. Method: The Cochrane Hepato-Biliary Specialised Register was searched to identify (quasi-) RCTs to include in our meta-analysis. Two authors independently reviewed each study. Primary outcomes were haemostatic efficacy (defined as haemostasis within 4 or 5 minutes post application), adverse events and perioperative mortality (within 30-days of surgery). Statistical analyses were performed using the random effects model and results expressed as odds ratio (OR) with 95% confidence intervals. Result: Twenty-seven RCTs (3736 participants) were included in our analysis. FBHAs were found to have superior haemostatic efficacy compared to NFHAs (OR 4.03; 1.73–9.36, p=0.001), and were superior to SoC (OR 13.59; 4.06–45.47, p<0.0001). Incidence of adverse events and perioperative mortality was no different when comparing FBHAs with SoC or NFHAs. No differences were detected when testing for post-operative bile leakage, intra-abdominal collections, volume of abdominal drain output, post-operative transfusion requirements, reoperation rates and length of stay (all p>0.05). Conclusion: FBHAs appear superior to SoC and NFHAs in achieving haemostasis within 4–5 minutes post-application, however this does not translate into improved post-operative outcomes. FBHAs are not justified for routine use based on the available evidence.